2020
DOI: 10.5688/ajpe7805
|View full text |Cite
|
Sign up to set email alerts
|

A Co-Curricular Activity to Introduce Pharmacy Students to the Concepts of Innovation and Entrepreneurship

Abstract: To develop, implement and evaluate a 'Shark Tank' style co-curricular activity focusing on creating a new clinical pharmacy service, including assessing student performance and determining the effect of the activity on students' perceptions of innovation as it applies to their own future practice and pharmacy practice in general. Methods. Second year pharmacy students participated in an optional 'Shark Tank' style co-curricular activity and worked in teams to develop a clinical service. A team of faculty grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Students may be exposed to these concepts through student professional organizations, 17,18 elective courses, 19 or co-curricular activities. 20 Mogul et al reported on a co-curricular activity, modeled after the popular television series SharkTank. 20 Students (n=38) were assigned teams and tasked with developing a solution (or pitch) to a pharmacy services related problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students may be exposed to these concepts through student professional organizations, 17,18 elective courses, 19 or co-curricular activities. 20 Mogul et al reported on a co-curricular activity, modeled after the popular television series SharkTank. 20 Students (n=38) were assigned teams and tasked with developing a solution (or pitch) to a pharmacy services related problem.…”
Section: Discussionmentioning
confidence: 99%
“…20 Mogul et al reported on a co-curricular activity, modeled after the popular television series SharkTank. 20 Students (n=38) were assigned teams and tasked with developing a solution (or pitch) to a pharmacy services related problem. Faculty evaluated students using a standardized rubric and students completed a pre-and post-program survey.…”
Section: Discussionmentioning
confidence: 99%
“…2 There are numerous strategies for achieving competencies in business management and entrepreneurship. These competences can be acquired through required didactic courses, [3][4][5][6][7][8] electives, [9][10][11] co-curricular activities, 12 workshops, 13 experiential rotations, 14 or a combination of strategies. Courses can focus on initiatives in ambulatory care, 9 mass merchandise pharmacy, 3 community pharmacy, 6,10,15,16 clinical pharmacy, 5,7 or students can have the freedom to choose from an array of business ideas.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, not all pharmacy schools are equipped with the requisite resources, nor is it their priority to provide such intensive learning opportunities. Although there are numerous reports emphasising the significance of entrepreneurial development in pharmacy students (Hermansen-Kobulnicky & Moss, 2004;Huston, 2018;Mattingly et al, 2019a), there are very few studies related to implementation and assessment of IE activities (Laverty et al, 2015;Mogul et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Laverty and colleagues offered a workshop that teaches undergraduate pharmacy students about entrepreneurship and evaluated the outcomes using the Shark Tank model (Laverty et al, 2015). Mogul and colleagues implemented and evaluated an innovative clinical service model to solve a pharmacy related issue using the Shark Tank approach (Mogul et al, 2020). However, during the recent COVID-19 pandemic crisis, exploring novel platforms of instilling entrepreneurship skills were the need of the hour.…”
Section: Introductionmentioning
confidence: 99%